EEG Markers in Emotionally Unstable Personality Disorder—A Possible Outcome Measure for Neurofeedback: A Narrative Review. (July 2021) - Boland, Cailín; Jalihal, Virupakshi; Organ, Catriona; Oak, Katy; McLean, Brendan; Laugharne, Richard; Woldman, Wessel; Beck, Randy; Shankar, Rohit
Objectives . There is growing evidence for the use of biofeedback (BF) in affective disorders, dissocial personality disorder, and in children with histories of abuse. Electroencephalogram (EEG) markers could be used as neurofeedback in emotionally unstable personality disorder (EUPD) management especially for those at high risk of suicide when emotionally aroused. This narrative review investigates the evidence for EEG markers in EUPD. Methods . PRISMA guidelines were used to conduct a narrative review. A structured search method was developed and implemented in collaboration with an information specialist. Studies were identified via 3 electronic database searches of MEDLINE, Embase, and PsycINFO. A predesigned inclusion/exclusion criterion was applied to selected papers. A thematic analysis approach with 5 criteria was used. Results . From an initial long list of 5250 papers, 229 studies were identified and screened, of which 44 met at least 3 of the predesigned inclusion criteria. No research to date investigates EEG-based neurofeedback in EUPD. A number of different EEG biomarkers are identified but there is poor consistency between studies. Conclusions . The findings heterogeneity may be due to the disorder complexity and the variable EEG related parameters studied. An alternative explanation may be that there are a number of different neuromarkers, which could be clustered together with clinical symptomatology, to give new subdomains. Quantitative EEGs in particular may be helpful to identify more specific abnormalities. EEG standardization of neurofeedback protocols based on specific EEG abnormalities detected may facilitate targeted use of neurofeedback as an intervention in EUPD.